When the attraction of Ta’ziyeh is diminished, the community should inevitably find a suitable replacement for it - Alizadeh, F.; Hashim, M.N. (Cogent OA, 2016)
This article studies the influence of form and content of Ta’ziyeh on theatre alongside replacement of Ta’ziyeh in modern theatre by eclectic theatre. In order to investigate and critic the character of Ta’ziyeh on modern theatre, Ta’ziyeh and its influence of artists works are analysed. This raises the question, Is Ta’ziyeh only a traditional, symbolic and unrealistic form of theatre, incomparable to other theatrical styles, or it needs to be focused with evaluation of traditional ceremonies? To address this question, we analysed some theatre productions based on eclectic theatre.